An Analysis of Speaking Problems in E-Learning due to COVID-19: A Case Study of the 6th Semester English Study Program Students at University - Irawan, Stefanie; Eliwarti, Eliwarti; Syarfi, Muhammad (Institut Agama Islam Negeri Palopo, 2023)
Students encounter difficulties when it comes to speaking in online classes, particularly when they are navigating this new era of E-learning during the pandemic. This research aims to find out the speaking problems in E-learning due to covid-19 faced by the 6th semester students of the English Study Program of FKIP Universitas Riau. This research is a descriptive study with a mixed method research. The total of respondents are 74 students. The data collection methods used are questionnaire and interview. The data analysis techniques include data collection, data reduction and conclusion. Based on the research results, it can be concluded that the students experience speaking problems in E-learning due to Covid-19 in three ways: psychological (inhibition, shyness, and anxiety, lack of self-confidence, and lack of motivation), environmental (environmental aspects that make up the learning atmosphere in E-learning), and technological (network problems and facility issues). The most common speaking problems in E-learning due to covid-19 encountered by the 6th semester students of the English Study program at FKIP Universitas Riau are inhibition (mean score of 4.85 and 89,2% students choose strongly agree), an unstable network (mean score of 4.80 and 84,2% students choose strongly agree), and a discouraging environment (mean score of 4.78 and 78,4% students choose strongly agree).